2005
DOI: 10.1161/01.hyp.0000188703.27002.14
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Is as Important as Proteinuria in Identifying Fetal Risk in Women With Gestational Hypertension

Abstract: Abstract-Gestational hypertension is differentiated into higher and lower risk by the presence or absence of proteinuria.We asked if hyperuricemia, a common finding in pregnancy hypertension, might also be an indicator of increased risk. We examined fetal outcome data from 972 pregnancies collected from 1997 to 2002 in a nested case-control study. Participants were nulliparous with no known medical complications. The frequency of preterm birth, the duration of pregnancy, frequency of small-for-gestational-age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
182
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(212 citation statements)
references
References 19 publications
19
182
0
11
Order By: Relevance
“…This finding is in accordance with the study done by Punthumapol et al [19]. It is found that estimation of serum UA is as important as proteinuria in identifying the risk of renal involvement and fetal compromise [20]. Maternal hyperuricemia is found to be a strong predictor of maternal disease progression and fetal outcome.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with the study done by Punthumapol et al [19]. It is found that estimation of serum UA is as important as proteinuria in identifying the risk of renal involvement and fetal compromise [20]. Maternal hyperuricemia is found to be a strong predictor of maternal disease progression and fetal outcome.…”
Section: Discussionsupporting
confidence: 92%
“…However, the inclusion of these women is consistent with the additional risks surrounding hyperuricemia 21 and with our wider aim of developing a generalizable model.…”
Section: Predicted Probability Predicted Probabilitymentioning
confidence: 57%
“…Concretamente, en relación a los resultados adversos en el recién nacido, Roberts y cols. 3 mostraron que las mujeres hipertensas e hiperuricémicas, tienen mayor riesgo de diagnóstico de bajo peso para la edad gestacional (~3 veces) o parto < 37 semanas (~10 veces). Evidencia confirmada por otro grupo en Australia 19 .…”
Section: áCido úRico Y Pre-eclampsiaunclassified
“…E l ácido úrico, producto final del metabolismo de las purinas, es utilizado como marcador de daño renal y factor de riesgo de morbilidad materna y neonatal en embarazos con pre-eclampsia [1][2][3] . Así, las mujeres hipertensas e hiperuricémicas tienen mayor riesgo de parto pretermino, retardo de crecimiento intrauterino (RCIU) y pre-eclampsia de origen temprano (< 34 semanas), que aquellas mujeres con embarazos normales o mujeres pre-eclámpticas sin hiperuricemia 3,4 .…”
unclassified
See 1 more Smart Citation